2022
DOI: 10.1186/s12877-022-03634-y
|View full text |Cite
|
Sign up to set email alerts
|

Examining the predictors of healthcare facility choice for outpatient care among older adults in India using Andersen’s revised healthcare utilization framework model

Abstract: Background In India, the demand for outpatient care is substantially higher than inpatient care among older adults. Therefore, the current study examines the level, patterns, and factors associated with outpatient care use. Methods The present research used data from the first wave of the Longitudinal Ageing Study in India (LASI, 2017–18). A total of 34,588 older adults (45 years and above) who accessed outpatient healthcare services in one year pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…This highlighted the need for policies that specifically target underprivileged regions and social groups. Rahaman et al (2022) examined healthcare facility choices among older adults using Andersen's revised healthcare utilization framework. Their research, based on a survey of older adults, identified factors like health needs, enabling resources, and personal health practices as key determinants in healthcare facility choices.…”
Section: Review Of Scholarly Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlighted the need for policies that specifically target underprivileged regions and social groups. Rahaman et al (2022) examined healthcare facility choices among older adults using Andersen's revised healthcare utilization framework. Their research, based on a survey of older adults, identified factors like health needs, enabling resources, and personal health practices as key determinants in healthcare facility choices.…”
Section: Review Of Scholarly Workmentioning
confidence: 99%
“…The decision-making process in healthcare utilization, particularly among older adults, is another crucial aspect of this discourse. Rahaman et al (2022) examine the factors influencing healthcare facility choices among the elderly. Their study applies Andersen's revised healthcare utilization framework to understand these choices better.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, in this study, the probabilities of self-rated health among the older adult floating population with junior high school, high school, and college or higher education are 3.49 times, 1.61 times, and 4.90 times that of those with primary school or lower education, respectively, far higher than the probability multiples of 1.68, 1.79, and 1.61 in another study. The health status differences between the older adults with different levels of education, compared to non-migrants, may result in greater differentiation, which calls for further research ( 42 ). Secondly, although some studies have revealed that marriage helps maintain health by protecting people from physical and emotional stress and harmful health behaviors ( 43 , 44 ), this study did not find a statistically significant difference in the health status of older adult migrants with or without spouses.…”
Section: Conclusion and Policy Implicationmentioning
confidence: 99%
“…16 Many previous researchers have used the framework to investigate aspects of healthcare decision-making, healthcare facility selection, and healthcare system efficiency in both developed and developing countries. [16][17][18][19][20] Furthermore, the effectiveness of Andersen's defined factors for selecting a healthcare unit is observed to significantly change with demographic, geographical, and cultural differences. [19][20][21] Previous studies have explored the factors associated with healthcare choice among the growing older adult population in India using Andersen's revised framework.…”
Section: Rahaman Et Almentioning
confidence: 99%
“…[19][20][21] Previous studies have explored the factors associated with healthcare choice among the growing older adult population in India using Andersen's revised framework. 13,17 However, the studies were limited to explore socioeconomic inequality in the healthcare choice for outpatient care among older adults in India. With this backdrop, the present research aimed to add to the literature on the association of socioeconomic inequality of health service utilization for outpatient care among older adults in public, private, and other facilities in India.…”
Section: Rahaman Et Almentioning
confidence: 99%